Evaluation of Grey Relation between Chaotic Characteristic and Uncertainty of Rolling Bearing Vibration Performance - Liang Ye; Xintao Xia; Zhen Chang (Jixie chuandong)
In view of the variability， non-linearity and uncertainty of failure probability distributions of rolling bearing vibration performance， the Hurst index and maximum entropy index of vibration data series are proposed to represent the chaotic characteristics and uncertainty of the rolling bearing vibration performance， respectively. Based on the vibration data series of rolling bearing in service， the Hurst index is obtained using least square method in logarithmic coordinate system， and the chaotic characteristic of bearing operation performance state is judged in the corresponding time period of each vibration sequence. The maximum value of entropy of each vibration sequence is solved by utilizing the maximum entropy method， so as to quantitatively analyze the uncertainty of bearing vibration performance. To analyze the nonlinear correlation degree between chaotic characteristics and uncertainty of bearing vibration performance， the grey relation analysis method is applied to calculate the grey confidence level between Hurst index and maximum entropy sequence after mean normalization. In the two cases， the grey confidence levels between Hurst index and maximum entropy sequence are 96.99% and 82.1%， respectively， which show that the relationship between chaotic characteristics and uncertainty of bearing vibration performance is very close.